Empowerment of the Talango Islands Community Sumenep Regency through digital printing and screen printing business - Budi Dwi Satoto; Bain Khusnul Khotimah (Berdikari: Jurnal Pengabdian Masyarakat Indonesia, 2019)
The role of youth in development is very important because it is considered productive age to support various development activities in various sectors. Most youth can be absorbed in the labor market, and partly eliminated from the competition become static group. Not a few who engage in Small and Medium Enterprises such Silk Screen Printing. However, the form of efforts among youth most still use manual design and printing due to lack of capital and expertise. With this activity, try to solve them with IbM is working with partners Silk Screen Printing Industry centers in villages Talango, Talango islands, Sumenep, Disperindag and local cooperative activities such as application of digital printing printing techniques, the design theme of local wisdom Madura images with color or multicolor monocolor and entrepreneurship training and business management. IbM activity is done in the form of training, coaching and mentoring the youth group field of screen printing and printing for souvenirs and handicrafts which aims to: 1) increase the motivation of entrepreneurial partners; 2) improve the understanding of partner business planning and business management; 3) improve human resource capabilities in the production and marketing techniques; 4) develop a network to support youth entrepreneurship development of the creative economy. Youth empowerment group is expected to produce a model that can be used as a model youth entrepreneurial development youth empowerment-based society.